If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying S + (S + 11100) = 49500 Reorder the terms: S + (11100 + S) = 49500 Remove parenthesis around (11100 + S) S + 11100 + S = 49500 Reorder the terms: 11100 + S + S = 49500 Combine like terms: S + S = 2S 11100 + 2S = 49500 Solving 11100 + 2S = 49500 Solving for variable 'S'. Move all terms containing S to the left, all other terms to the right. Add '-11100' to each side of the equation. 11100 + -11100 + 2S = 49500 + -11100 Combine like terms: 11100 + -11100 = 0 0 + 2S = 49500 + -11100 2S = 49500 + -11100 Combine like terms: 49500 + -11100 = 38400 2S = 38400 Divide each side by '2'. S = 19200 Simplifying S = 19200
| -2(t-3)=3(t+1) | | 8x-4-5x=-31 | | 10=2.5 | | 5N+10(N+7)=430 | | 0=-3x^2+12x+15 | | y-0.7=-22 | | -32a-8=-136 | | 28n+17=38 | | 3x=6+5y | | 17(A)+3(6A)=210 | | 3z+6=7z-30 | | y=.8x^3-2.1x^2-4x+5 | | 3x^4-20x^2-23=0 | | 2(1-a)=3(1+2a)+5 | | S(p)=p^2+14p+35 | | 33y+66=-9 | | -12d-8=-4(d+2)-8d | | 8w+8(8w)=132 | | 5b^9-5b^8-10b^7= | | 11(d+6)=2(d-7)+9d | | (n^2+9n+20)=0 | | -24s-53=49-s | | 0=a^2+0.5 | | 6x+2(x-1)=30+10x | | 2w+2(2w)= | | 4t-7=18-m | | 2w+2(2w)=162 | | 6+2k=-4 | | 6(2+y)= | | x-67=x+127 | | -3+d=15 | | 8w-11w=18 |